The Merriam-Webster dictionary (Springfield, MA, 2004)
This language reference consists of 65000 entries covering the core vocabulary of everyday life. It offers more than 75,000 definitions. It also Includes pronunciations, word origins, and synonym lists
Keywords: English language; Tiếng Anh